Analisis kualitas pelayanan terhadap kepuasan konsumen pada Indika Kreasindo Event Organizer Pekanbaru - Rangga Fajra Pradipta; Aida Nursanti; Chairul Amsal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The best service and quality is very helpful in order to maintain consumer Indika Kreasindo Event Organizer.The aim of this study was to determine the quality of services provided by Indika Kreasindo Event Organizer to their subscriber gaps between customer expectations regarding the quality of services provided by the company to the customer.This study was conducted by distributing questionnaires to customers Indika Kreasindo Event Organizer randomly selected to obtain the original data on expectations and performance that can indicate the level of customer satisfaction. This questionnaire is a tool used in the method servqual (Parasuraman et.al), consists of 30 of the questions that have been adapted to Indika Kreasindo event organizer and have tested the validity and relibitasi expectations and performance of the 72 consumers.From the research that has been done, the quality of service is obtained consisting of physical evidence (tangible), empathy (empathy), reliability (reliability), responsiveness (responsiveness), guarantee (assurance) is positive, this indicates that the quality of service Indika good Kreasindo Event Organizer partially and simultaneously meet customer expectations. In this study the most influential variable is the variable reliability (X3) with a value of 11.151. The advice given to the Event Organizer Indika Kreasindo is that maintaining the service dimension that already meet consumer expectations.Keywords: Quality of Service and Customer Satisfaction.